Outcrossing rates and organelle inheritance estimated from two natural populations of the Japanese endemic conifer Sciadopitys verticillata - Worth, James R. P; Yokogawa, Masashi; Isagi, Yuji (Journal of Plant Research, 2014)
The Japanese endemic conifer Sciadopitys verticillata is one of the most phylogenetically isolated species of all plants. Occurring in small and scattered populations, the species is currently classified as Near Threatened by the International Union for Conservation of Nature and Natural Resources (IUCN) and as Vulnerable in three prefectures of Japan. This study investigated two major factors that should impact the genetic structure of the species at both the nuclear and organelle DNA level, the mating system and the inheritance of both the chloroplast and mitochondrial genomes. The mating system is crucial to determining the degree of outcrossing of plant species and thus should have a key role in shaping the species’ population level genetic diversity and gene flow between populations but as yet has not been studied in S. verticillata. Nine mother trees and their seedling progeny from two natural populations were genotyped using genetic markers from three plant genomes (eight nuclear microsatellites and DNA sequence for the chloroplast and mitochondria). Using a maximum likelihood method implemented in the software MLTR, the study found an outcrossing rate in the seedling stage of 0.49 and 0.79 for Aburazaka and Mount Shirotori populations, respectively, and an average of 0.66 at the species level. These outcrossing rates were low for conifers and therefore may have potential deleterious implications for the conservation of the species. The test of organelle inheritance supported paternal transmission of both the chloroplast and mitochondria consistent with previous microscopic evidence.